Proteins Characterization in The Skin Mucus of Mutiara Catfish (Clarias Gariepinus) by Using SDS Page Electrophoresis Method - Hanami, Cindy Claudea (Bioscientist : Jurnal Ilmiah Biologi, 2025)
Fish have a body defense system to protect themselves from various threats originating from the aquatic environment. One of the outermost defense mechanisms in the fish body is skin mucus. Mucus on fish skin is composed of water, glycoproteins, enzymes, antibodies, and other organic compounds. Through proteomic screening analysis, we can investigate the types and abundance of major proteins in fish mucosal exosomes. The aim of this study was to analyze the molecular weight of proteins in the surface mucus of mutiara catfish, and to identify the proteins detected in the mucus of mutiara catfish. The research method uses a descriptive method. The characterization process using SDS-PAGE. Analysis of protein molecular weight is obtained by measuring the displacement distance (Rf) in the sample. The molecular weight of proteins detected in mutiara catfish mucus had a molecular weight of 7.10 kDa, 13.51 kDa, 15.46 kDa, 28.78 kDa, 30.72 kDa, 42.40 kDa and 69.17 kDa. Proteins found abundantly in the mucus on the surface of catfish skin have a molecular weight ranging from 7-15 kDa, where this protein has various roles including immune defense, regulation of metabolism, oxidative stress, and the nervous system, stress regulation, regulation of cellular function, muscle contraction, and nervous system function. It can be concluded that the proteins found in the mucus on the surface of catfish skin are mostly small-sized proteins and have a major role in body defense, immune protection, and adaptation to environmental stress. These proteins are very important in maintaining fish health.